Islam dalam Politik Indonesia - Mubarak, Haris Zaky (IAIN Surakarta, 2018)
One of the important political dynamics of the Soeharto administration was the question of the activeness of scholars in Indonesia's practical political activities. This study shows that the emergence of ulama who actively participated in politics and in the Islamic party at that time namely the United Development Party (PPP) was not only interpreted as a face of political expression of Muslims but also as a large colonization of the current regime against the political aspirations of Indonesian Muslims. PPP was raised by the New Order regime as part of the politics of colonization as well as maximizing the existence of Golkar as a silencer for Islamic political groups. The existence of Golkar during the New Order did not only act as a force for the interests of the New Order but also became a reliable communicator in the practice of national politics. Islamic political discourse on various issues of development and unity has always been reduced by the government for the sake of the solid political legitimacy of the New Order government.